Potential use of data mining techniques in information technology consulting operations - Qadri, Mehran; Ahmad, Zubair; Ibrahim, Jamaludin (IJSRP.ORG, 2015)
The concept of data mining has been around for a while now. It is a process of extraction of useful patterns and information from huge data sets. Many tools and techniques have been developed to make use of the data mining concept in various industries. However before implementing data mining techniques or making any other key decision relating to their I.T infrastructure, the top management of a business would usually consult with an I.T consulting firm to determine the feasibility of adopting new techniques such as data mining into their business operations. An I.T consulting firm, in turn will provide the client with valuable feedback in the form of advice, or cost estimations and potential profits, or even a full-fledged plan on how to implement techniques like data mining into their business. However, the question does arise as to whether I.T consulting firms themselves should implement data mining techniques into their business operations and whether such techniques can help them to provide better services to their clients. I.T consulting firms advise clients on a range of areas related to I.T such as strategic planning, security consulting, networking, systems integration etc. This means that an I.T consulting firms has to manage and sustain a huge network of clients, partners, and service providers. This, then naturally results in a huge amount of data that is to be stored and maintained by the firm. This paper will discuss the concept of data mining, the use of data mining in other industries and its benefits, its potential use by I.T consulting firms, and whether it can help improve I.T consulting operations.